1992
DOI: 10.1177/0145482x9208600407
|View full text |Cite
|
Sign up to set email alerts
|

Employment Concerns of People with Blindness or Visual Impairments

Abstract: Seventy-six consumer members of the American Council of the Blind with primary disabilities of blindness or visual impairment responded to an Employment Concerns Questionnaire which was developed by consumers, advocates, and service providers. Respondents’ concerns included their not receiving adequate help in developing job search strategies, in obtaining information on career opportunities, and in financing assistive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 4 publications
1
32
0
1
Order By: Relevance
“…ES CI MA AM LD NS RS PC QIs met Bell and Mino (2013) Cimarolli and Wang (2006) Crudden and Hanye (1999) Leonard, D'Allura, and Horowitz (1999) Roessler, and Schriner (1992) N significant relationships between race/ethnicity and employment or earnings. Gender was included in four analyses in three studies.…”
Section: Studymentioning
confidence: 99%
“…ES CI MA AM LD NS RS PC QIs met Bell and Mino (2013) Cimarolli and Wang (2006) Crudden and Hanye (1999) Leonard, D'Allura, and Horowitz (1999) Roessler, and Schriner (1992) N significant relationships between race/ethnicity and employment or earnings. Gender was included in four analyses in three studies.…”
Section: Studymentioning
confidence: 99%
“…Bureau of Labor Statistics, 2019b, 2019a). A substantial amount of research has also supported the importance of higher education for employment outcomes of people with visual impairments (i.e., those who are blind or have low vision; Capella-McDonnall, 2005; Cimarolli & Wang, 2006; Cmar et al, 2018; Giesen & Cavenaugh, 2013; Leonard et al, 1999; McDonnall, 2016; Wolffe et al, 1992). Recent systematic literature reviews have documented the significant association between education and employment for this population (Lund & Cmar, 2019a, 2019b).…”
mentioning
confidence: 99%
“…Three studies of employment and vision impairment conducted in the US have been reported in the peer‐reviewed literature 4 –6 . Employment rates were reported to be 57% in consumer members of the American Council of the Blind who were aged 17–71 years, 5 36% in recent graduates of the Texas School for the Blind, 6 and 44% in clients of the Illinois Bureau of Blind Services 4 .…”
Section: Discussionmentioning
confidence: 99%